PEGDA hydrogel structure from semi-dilute concentrations: insights from experiments and molecular simulations. Issue 18 (25th April 2022) - Mercado-Montijo, Jomary; Anstine, Dylan M.; Rukmani, Shalini J.; Colina, Coray M.; Andrew, Jennifer S.
Abstract : A combined experimental and computational approach highlights the connection of polymer chain interactions with hydrogel structure and performance. This work provides a foundation for the design of hydrogels for applications beyond dilute conditions. Abstract : The efficacy of hydrogel materials used in biomedical applications is dependent on polymer network topology and the structure of water-laden pore space. Hydrogel microstructure can be tuned by adjusting synthesis parameters such as macromer molar mass and concentration. Moreover, hydrogels beyond dilute conditions are needed to produce mechanically robust and dense networks for tissue engineering and/or drug delivery systems. Thus, this study utilizes a combined experimental and molecular simulation approach to characterize structural features for 4.8 and 10 kDa poly (ethylene glycol) diacrylate (PEGDA) hydrogels formed from a range of semi-dilute solution concentrations. The connection between chain–chain interactions in polymer solutions, hydrogel structure, and equilibrium swelling behavior is presented. Bulk rheology analysis revealed an entanglement concentration for PEGDA pre-gel solutions around 28 wt% for both macromers studied. A similar transition in swelling behavior was revealed around the same concentration where hydrogel capacity to retain water was drastically reduced. To understand this transition, the hydrogel structure was characterized using the swollen polymer network hypothesis and compared to pore size distributions from molecular dynamics simulations. We find in both approaches a structural transition concentration at the hydrogel swelling inflection point that is comparable to the entanglement concentration. Calculated mesh sizes from theory are compared with computationally determined average maximum pore diameters; mesh sizes from theory yielded greater feature sizes across all concentrations considered. Molecular simulations are further used to assess pore dynamics, which are shown to vary in distribution shape and number of modes compared to the time-averaged hydrogel pore features. Altogether, this work provides insights into hydrogel network features and their dynamic behavior at physiological conditions (37 °C) as a basis for hydrogel design beyond dilute conditions for biomedical applications.